2015
DOI: 10.3892/or.2015.4524
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124-3p inhibits the growth and metastasis of nasopharyngeal carcinoma cells by targeting STAT3

Abstract: The present study investigated the effects of microRNA-124-3p (miR-124-3p) expression on nasopharyngeal carcinoma (NPC) cells and its relevant mechanism. A total of 90 NPC tissues and 85 postnasal catarrh tissues were collected. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect tissue samples and expression of miR-124-3p in CNE1, CNE2, SUNE1, H0NE1, 5-8F, 6-10B and C666-1 NPC cell line and immortalized nasopharyngeal epithelial cells line (NP69). Overexpressed miRNA-124-3p in CNE-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 45 publications
4
37
0
1
Order By: Relevance
“…In addition, the overexpression of miR-124 resulted in the inhibition of cell proliferation and invasion in NPC cells. In agreement with our findings, previous studies revealed that overexpression of miR-124 dramatically suppressed cell proliferation, colony formation, migration, and invasion of NPC by targeting STAT3 or Foxq1 12,13. All these findings suggest that miR-124 functions as a tumor suppressor in NPC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the overexpression of miR-124 resulted in the inhibition of cell proliferation and invasion in NPC cells. In agreement with our findings, previous studies revealed that overexpression of miR-124 dramatically suppressed cell proliferation, colony formation, migration, and invasion of NPC by targeting STAT3 or Foxq1 12,13. All these findings suggest that miR-124 functions as a tumor suppressor in NPC.…”
Section: Discussionsupporting
confidence: 93%
“…In consistent with our findings, Cai et al26 revealed that miR-124 suppressed the migration and invasion of glioma cells by targeting Capn4. Previous studies also have demonstrated that miR-124 inhibited the proliferation and invasion of NPC cells by modulating its functional targets, such as STAT3 and Foxq1 12,13. All these findings suggest that miR-124 regulates different targets in NPC.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Another significant result of our study is that the up‐regulated miR‐124‐3p could accelerate the apoptosis as well as cell cycles in HCC. In line with this outcome, the promotive impacts of miR‐124‐3p on apoptosis of nasopharyngeal carcinoma cells have been reported in an existing research . In addition, Zhang et al have also discovered that the overexpression of miR‐124‐3p has the ability to repress the apoptosis and cell cycle arrest in glioblastoma multiforme through regulating NRP‐1 .…”
Section: Discussionmentioning
confidence: 64%
“…The dysregulation of p53 or its associated miRNAs has been reported to confer resistance against apoptosis in cancer cells. Moreover, apoptosis is induced by the overexpression of miR-101 in human BCC via modulating JAK2 [115] and by miR-124-3p in nasopharyngeal carcinoma via modulating STAT3 and its downstream targets [116]. Yan et al [114] have demonstrated that upregulation of miR-17-92 cluster in tumor cells can evade hypoxia-triggered apoptosis.…”
Section: The Role Of Mirnas In Counteracting Cancer Cell Apoptosismentioning
confidence: 99%